Macklemore & Ryan Lewis : Grammy-winning hip-hop duo - Cummings, Judy Dodge (Essential Library, an imprint of Abdo Pub., 2015)
A look at the lives and careers of Grammy-winning hip-hop artists Macklemore and Ryan Lewis.